Dialogue with Asian Realities: The Vision of the Asian Church as Communion - Ravichandran, M.V.E. (University of jaffna, 2024)
The Federation of Asian Bishops’ Conferences (FABC) in response to the call of the Vatican II to become the People of God has been trying to build up the Asian Church as a communion. Asia is a continent blessed with many ethnicities, cultures and religions. Unfortunately this pluralism is not appreciated in many countries; instead it erupted into terrible violence in some countries. Therefore the research problem addressed in this study is how the Church in Asia under the guidance of the FABC is trying to promote communion within the Church and with the other related stakeholders. Thus the hypothesis of this research is that the Church in Asia is trying to promote peace and harmony in the Asian society by becoming an agent of communion. The methodology adopted in this research is basically qualitative and analytical. Textual analysis will be the main data collecting method. The primary and secondary documents are studied critically and the conclusions drawn through deductive analysis. As the results of this research it is identified that the FABC is proposing incluturation, contextualization and inter-religious dialogue so that the Church in Asia will become an agent of communion, solidarity and harmony. FABC tries to promote tolerance, coexistence and harmony which are the much wanted values in Asia. The focal point of the reflections of FABC is the triple dialogue; the dialogue with the poverty, cultures and religions of Asia. To attain this it has developed a pastoral tool namely Asian Integral Pastoral approach (AsIPA) which is designed to train people in forming Small Christian Communities and Basic Human Communities. Therefore the vision of the Church as communion of FABC will benefit not only the Church but also the Asian society at large.
Keywords: Communion; FABC; Church; dialogue; Asia